Efficacy of Sunitinib in Turkish Patients with Gastrointestinal Stromal Tumors; Retrospective Multicenter Experience - DANE, FAYSAL (H G E UPDATE MEDICAL PUBLISHING S A, 2013)
Background/Aims: Sunitinib is a multi-targeted thyrosine kinase receptor inhibitor used in patients with advanced gastrointestinal stromal tumours (GISTs). We evaluated the efficacy and tolerability of sunitinib therapy in Turkish patients with GISTs. Methodology: Between January 2001 and April 2012, 57 patients who had progressive disease or experienced unacceptable toxicity during imatinib treatment from multiple centers were investigated retrospectively. Results: Thirty-three patients were male and 24 were female. The median age was 55 years (range; 16-84 years). Thirty-eight of the patients received imatinib for longer than 12 months, 13 patients received for 6-12 months, and 6 patients received for less than 6 months. The clinical benefit of sunitinib was 73.7%. Treatment-related adverse events were reported in 78% of the patients. Adverse events were generally mild to moderate in intensity The median progression free survival (PFS) and overall survival (OS) of the patients that received sunitinib were 10.8 months and 23.9 months, respectively. The time of imatinib usage and response to sunitinib were independent prognostic factors for PFS and OS. Also, tumor size was an independent prognostic factor for PFS. Conclusions: Sunitinib is an effective treatment in Turkish patients with GISTs, with a clinical benefit of 73.7% and shows an acceptable tolerability
Keywords: GISTs; Sunitinib; Imatinib intolerance; TYROSINE KINASE INHIBITOR; IMATINIB MESYLATE; GROWTH-FACTOR; C-KIT; PROGNOSTIC-FACTORS; IN-VITRO; SU11248; MUTATIONS; MANAGEMENT; TAIWANESE